Fe3O4@PA6/MWCNT composites with multiple gradient segregated structures for electromagnetic shielding with low reflection. Issue 19 (29th January 2022) - Wu, Bozhen; Zhu, Kaiqi; Wen, Xinghan; Li, Minpei; Yang, Yuhao; Yang, Jintao
Abstract: Green electromagnetic interference (EMI) shielding materials have been popularly accepted as the most promising EMI shielding material used in the electronic industrial community. Nevertheless, the design and optimization for both material and structure to achieve this function remain many challenges. Herein, Fe3 O4 @PA6 microspheres were fabricated by an unusual reaction‐induced phase separation method, where Fe3 O4 nanoparticles were in situ introduced into the polymerization system. Interestingly, most Fe3 O4 nanoparticles spontaneously immigrated into PA6 microsphere, forming Fe3 O4 @PA6 composite microspheres, and more interestingly, the saturation magnetization and particle size of the microspheres are highly associated. Therefore, the microspheres with specific particle size and magnetic property were easily obtained by simple sieving. These microspheres were then coated by MWCNT and hot‐compressed into EMI materials with segregated structures. A multilayered structure with positive conductivity gradients and negative magnetic gradients were created. Due to this structure, electromagnetic wave can enter the materials from the impedance matching channel without a large amount of reflection on the surface. The results show that with the increase in the number of composite layers, the EMI SE increases to 24.8 dB, and the R‐value is significantly reduced to 0.51. This work provides a new feasible idea for designing low‐reflection EMI composites. Abstract : In this study, the method of combining caprolactam in‐situ anion polymerization and layer‐by‐layer powder coating was firstly used to design the preparation of nylon 6 electromagnetic shielding composites with multiple electromagnetic gradients. The results show that it has good electromagnetic shielding effectiveness and low‐reflection coefficient.